HIV and Malnutrition: Effects on Immune System - Shalini Duggal; Tulsi Das Chugh; Ashish Kumar Duggal (Clinical and Developmental Immunology)
HIV or human immunodeficiency virus infection has assumed worldwide proportions and importance in just a span of 25 years. Continuous research is being done in many parts of the world regarding its treatment and vaccine development, and a lot of money has flown into this. However, fully understanding the mechanisms of immune depletion has still not been possible. The focus has also been on improving the quality of life of people living with HIV/AIDS through education, counselling, and nutritional support. Malnutrition further reduces the capacity of the body to fight this infection by compromising various immune parameters. Knowledge of essential components of nutrition and incorporating them in the management goes a long way in improving quality of life and better survival in HIV-infected patients.